2020
DOI: 10.5194/egusphere-egu2020-6113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating CMIP6 Model Fidelity at Simulating Non-Gaussian Temperature Distribution Tails

Abstract: <p>Under global warming, changes in extreme temperatures will manifest in more complex ways in locations where temperature distribution tails deviate from Gaussian. For example, uniform warming applied to a temperature distribution with a shorter-than-Gaussian warm tail would lead to greater exceedances in warm-side temperature extremes compared with a Gaussian distribution. Confidence in projections of future temperature extremes and associated impacts under global warming therefore relies on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This highlights the utility of using the shift ratio to examine tails specifically. ERA5 shift ratio maps for both warm‐side and cold‐side tails closely resemble other observation‐based and model datasets (Catalano et al., 2020; Loikith & Neelin, 2019; Loikith et al., 2018).…”
Section: Shift Ratio Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…This highlights the utility of using the shift ratio to examine tails specifically. ERA5 shift ratio maps for both warm‐side and cold‐side tails closely resemble other observation‐based and model datasets (Catalano et al., 2020; Loikith & Neelin, 2019; Loikith et al., 2018).…”
Section: Shift Ratio Resultssupporting
confidence: 77%
“…(2016) demonstrated that trends in summer extremes over the historical period include significant changes in kurtosis and skewness, which could have an appreciable effect on the frequency of extremes as temperatures rise (Ballester et al., 2010; Clark et al., 2006). The latest ensemble of global climate models, CMIP6, skillfully captures coherent regions of non‐Gaussian tails (Catalano et al., 2020), so additional work analyzing the complexity of projected changes in the distribution of temperature extremes would be beneficial.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The new phase CMIP has incorporated further improved climate modules and thus is expected to yield improved representation of the Earth's climate system (Eyring et al, 2016). Evaluation of these new simulations with respect to the observed mean and extreme climates is drawing extensive research efforts (e.g., Catalano et al, 2020;…”
Section: Introductionmentioning
confidence: 99%
“…The new phase CMIP has incorporated further improved climate modules and thus is expected to yield improved representation of the Earth's climate system (Eyring et al., 2016). Evaluation of these new simulations with respect to the observed mean and extreme climates is drawing extensive research efforts (e.g., Catalano et al., 2020; Chen et al., 2020; D. Jiang et al., 2020; Rivera & Arnould, 2020; Xin et al., 2020), as it can inform the extent to which these models can be trusted for projecting future climate change and how they can be further improved. These studies demonstrated that the CMIP6 GCMs have an improvement in simulating the temporal and spatial patterns of the climate variables comparing to the previous phase (i.e., CMIP5).…”
Section: Introductionmentioning
confidence: 99%
“…Since the Coupled Model Intercomparison Project in Phase 6 (CMIP6) results are available, the extreme temperature events are widely evaluated and projected based on the multi-model simulations but most work focus on the change of climate extreme indices by the ETCCDI [3,12,22,36]. In this study, we aim to draw a risk map of extreme temperature events under climate change by estimating and comparing annual extreme high and low temperature values based on return level.…”
Section: Introductionmentioning
confidence: 99%